Psychological Impact of Acne Vulgaris in Basic Science Medical Students in Nepal - Eliz Aryal; Sanju Shrestha; Prashanna Shrestha; Govind Pokhrel; Sabina Sabina Bhattaria (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Acne vulgaris is a disorder of the sebaceous gland affecting mostly the adolescent age. Although acne does not cause direct physical impairment, it can produce significant psychosocial stress. Due to the paucity of data, there is a poor understanding of etiopathogenesis, treatment and psycho-social impact of acne in the Nepalese population. This study is the first of its kind in Nepal.